2015
DOI: 10.1353/cpr.2015.0085
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Investigation to Enhance Behavioral Health Referral for Perinatal, Low-Income Women With Mood Disorders

Abstract: Background Perinatal, low-income, ethnic minority women with mood disorders underutilize behavioral health treatment. A community–academic partnership was used to address behavioral health initiation among this population. Objectives We sought to examine the feasibility, acceptability, and preliminary outcomes of a behavioral health referral intervention with low-income, ethnic minority perinatal women diagnosed with mood disorders. Methods An open trial pilot study was conducted with 38 perinatal women. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This uptake rate is considerably lower than those in other screening programs, such as cancer screening (Yabroff et al, 2003;Callen et al, 2012;Dalton, 2018). Such a low Education Education on the definition, symptom and hazard of perinatal depression, prenatal depression or postnatal depression for women with positive screening results, mostly in the form of brochures (Miller et al, 2004;Flynn et al, 2006;Chen et al, 2011;Wisner et al, 2013;Bina, 2014;Boyd et al, 2015;BenDavid et al, 2016;Trost et al, 2016;Bauer et al, 2017;Jarvis et al, 2018).…”
Section: Comparison With Other Studies and Guidelinesmentioning
confidence: 98%
See 2 more Smart Citations
“…This uptake rate is considerably lower than those in other screening programs, such as cancer screening (Yabroff et al, 2003;Callen et al, 2012;Dalton, 2018). Such a low Education Education on the definition, symptom and hazard of perinatal depression, prenatal depression or postnatal depression for women with positive screening results, mostly in the form of brochures (Miller et al, 2004;Flynn et al, 2006;Chen et al, 2011;Wisner et al, 2013;Bina, 2014;Boyd et al, 2015;BenDavid et al, 2016;Trost et al, 2016;Bauer et al, 2017;Jarvis et al, 2018).…”
Section: Comparison With Other Studies and Guidelinesmentioning
confidence: 98%
“…Education on the definition, symptom and hazard of perinatal depression, prenatal depression or postnatal depression for women with positive screening results, mostly in the form of brochures (Miller et al, 2004;Flynn et al, 2006;Chen et al, 2011;Wisner et al, 2013;Bina, 2014;Boyd et al, 2015;BenDavid et al, 2016;Trost et al, 2016;Bauer et al, 2017;Jarvis et al, 2018).…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Three of the 19 studies that did not examine racial-ethnic differences in outcomes enrolled participants primarily from a mix of racial-ethnic minority groups (13,(35)(36)(37) (Table 2). These studies showed improvement in attendance of mental health clinics and reduced psychiatric hospitalization rates.…”
Section: Racial-ethnic Differences In the Initiation Of Mental Health Carementioning
confidence: 99%
“…Uebelacker et al's (41) telephone-based care management intervention for Latinos with depressive symptoms resulted in no difference in outpatient visits or receipt of antidepressants between the intervention and the control groups. Boyd and colleagues (35) showed that a behavioral health referral intervention based on identification of barriers, effective solutions, systematic follow-up, and psychoeducation with a case manager led to improvement in scheduling appointments for mental health services and in appointment attendance.…”
Section: Mental Health Interventionsmentioning
confidence: 99%